Technological dependence in Africa its nature, causes, consequences and policy derivatives - Fabayo, J. A.
Technology is critical to development because it is a resource which endows economic growth with much of its capacity for satisfying human wants. Whether the need is for more food, better education, improved housing, health care, transportation and telecommunication, increased industrial output, etc., modern technology plays a decisive role, particularly as it enhances the efficiency of resource utilization, spurs the creation and expansion of resources (e.g. physical capital) and diminishes the importance of natural factor endowment in economic progress. It is this developmental role of technology that makes its acquisition or the capability for generating it important and underscores the need for its importation in Africa, given the continent's inability to source it locally.
It is, however, the contention of this study that African countries' reliance on technology imports has not only inhibited local technological development efforts in the continent, but has also contributed, in a rather cumulative manner, to the distorted development or underdevelopment of the African economy. Unless concerted efforts are made to build up a strong indigenous scientific and modern technological development capability that can guarantee some degree of self-reliance in technological matters, any hope for a rapid and internally stimulated development of the African economy will remain as a mere illusion.
African countries' reliance on more developed countries via technology inputs is examined with the overall aim of ultimate self-reliance constantly in mind.
Keywords: Technological dependence--Africa.